On the Theory of Marriage Invalidity or Once Again on the Correlation between the Notions of “Void”, “Voidable” and “Inexistent” Marriage - Mateeva, Ekaterina (Yearbook of the Law Department, 2019)
The present article is devoted to one of the most debated issues in the theory of family law, namely the one concerning the legal notions of “void” and “inexistent” marriage and the correlation between them. From the perspective of legal history, the author traces the origin and the subsequent development of the different views upon these notions, expressed in the legal theory, initiating from the Roman private law until present day. This enables the conclusion that the issues on the precise legal qualification of a marriage as “inexistent”, “void” and “voidable” one and on the exact litigious manner by which both the respective legal vice of the marriage and the legal consequences of such a marriage are resolved, is subjected to a great extent to the dominant legal views – religious (canonical) or secular, on the institute of marriage and marriage formation throughout the development of society.